Chaos in the Shimizu-Morioka Model With Fractional Order - Wei, Zhangzhi; Zhang, Xin (Frontiers in Physics, 2021)
The investigation of dynamical behaviours for fractional order chaotic systems is a new trend recently. This paper is numerically concerned with a Shimizu- Morioka Model with fractional order. We find that chaos exists in the fractional order model with order less than 3 by utilizing the fractional calculus techniques, some phase diagrams are constructed also.